The Development of Fiqh Munākaḥah (Marriage Jurisprudence) Material Course in Madurese Islamic Universities and Its Relation with Gender Equality and Divorce Prevention - Maimun Maimun; Ainul Haq Nawawi; Abdul Haq Syawqi (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2020)
Abstract:Explanation of Law 1/1974, number 4 point e, obviously accentuates the principle of complicating divorce process such as requirement to have specific reasons and obligation to perform divorce in front of the court trial. The second is in line with article 115 of KHI (Kompilasi Hukum Islam; Islamic Compilation Book). These show how divorce requires prevention from both persons and institutions, including Islamic universities. Islamic universities have both academic and social responsibilities to prevent divorce due to their strategic duties and function in community development and empowerment, specifically for spreading knowledge, technology and artwork. This research aims to identify how far Madurese Islamic universities perform their roles and function by designing fiqh munakahat materials for its students as prospective husbands and wives. It focuses on whether the materials get developed and are compatible with gender equality and divorce prevention efforts. Using qualitative approach particularly its phenomenological type, this study took place in several Madurese Islamic universities. It revealed that the latest development of fiqh munakahat materials are still more about normative study from classical fiqh literature that it has no relevance to either gender equality spirit or divorce prevention effort.Abstrak:(Penjelasan UU Nomor I/1974, angka 4 huruf e, jelas menekankan prinsip untuk mempersukar perceraian dengan mewajibkan alasan-alasan tertentu serta mengharuskan proses perceraian dilakukan di depan siding pengadilan. Point kedua tersebut juga senada dengan KHI Pasal 115. Ini membuktikan bahwa perceraian harus dicegah oleh siapapun, baik perorangan ataupun instansi, termasukPerguruan Tinggi Islam. Perguruan Tinggi Islam memiliki tanggung jawab akademik dan social karena tugas dan fungsinya yang strategis dalam pengembangan dan pemberdayaan masyarakat, terutama dalam penyebaran pengetahuan, teknologi dan seni. Untuk mengetahui sejauh mana Perguruan Tinggi Islam di Madura menjalankan peran dan fungsinya tersebut, penelitian ini menelusuri kajian fiqh munakahat sebagai bahan konsumsi bagi calon-calon suami dan istri, khususnya apakah materi-materi tersebut sudah berkembang dan sesuai dengan wacana kesetaraan gender dan upaya pencegahan perceraian. Menggunakan pendekatan kualitatif berjenis fenomenologis, penelitian ini mengambil setting di beberapa Perguruan Tinggi Islam di Madura. Hasil penelitian menunjukkan bahwa perkembangan terbaru kajian fiqh munakahat masih didominasi kajian normative dari sumber fiqh klasik sehingga belum relevan dengan semangat kesetaraan gender maupun pencegahan perceraian).